Cost-effectiveness analysis of adopting rice methane mitigation measures in southern China - Chen, Kevin Z.; Hu, Shuang (CGIAR System Organization, 2025)
Rice production is a major source of agricultural greenhouse gas (GHG) emissions in China. In particular, methane emissions from paddy fields account for a substantial share, making rice systems a key point for achieving mitigation targets in the agricultural sector. In recent years, with the advancement of China’s carbon peaking and carbon neutrality strategies, low-carbon rice cultivation technologies have attracted growing attention. Across regions, a range of low-methane practices, such as alternate wetting and drying (AWD), optimized fertilizer management, improved straw utilization, direct seeding, and rice–upland crop rotation, have been promoted and adopted. However, systematic quantification remains limited regarding the differences across technologies in mitigation effectiveness, agroecological suitability, and economic costs. This gap constrains the identification of cost-effective mitigation pathways and the design of targeted policies. Meanwhile, much of the existing evidence relies on aggregate emission factors or region-level scenario analyses, and thus provides insufficient empirical evidence on the costs, benefits, and mitigation outcomes of these practices under farmers’ production conditions.